Half-Cutting as a Management Tool to Increase Abundance of Northern Bobwhite in South Texas - Dale A. Hall; Nova J. Silvy (National Quail Symposium Proceedings, 2017)
We evaluated the effectiveness of half-cutting honey mesquite (Prosopis glandulosa) trees to increase northern bobwhite (Colinus virginianus; hereafter bobwhite) habitat and abundance in South Texas. We compared the effects of half-cutting on the survival of mesquite and its effects on understory vegetation on both treated and control areas monthly. Data were taken under the tree’s canopy to determine understory plant species diversity, height, and density. We used bobwhite whistle counts, mark-recapture, and searched with trained dogs to determine the effects of half-cutting on bobwhite abundance. Half-cut young trees had 23.1% greater survival than did older half-cut trees. The area protected from grazing under half-cut trees was 10.2 times larger than that protected by control trees. Height of understory vegetation under half-cut trees was significantly (P = 0.005) taller then that under control trees. Treated areas supported more plant species than control areas but the difference was not significant (P = 0.072). Three bobwhite food plants had a positive response to half-cutting, whereas 3 were negatively affected. Half-cutting had no significant influence on numbers of cocks whistling (maximum 9 and 8 males calling/5-min period, respectively, for treatment and control). The number of bobwhite trapped on the half-cut area was 91 while only 75 were trapped on the control area. Trained bird dogs located 101 bobwhites on the half-cut areas and 78 on the control areas. The half-cut areas had the same number of coveys (10) as the control areas, however, covey sizes were larger (2.3 birds/covey) on the half-cut areas. We believe that half-cutting can add habitat and increase bobwhite abundance on many heavily grazed rangelands.
Keywords: abundance; Colinus virginianus; habitat; half-cutting; management; northern bobwhite; Texas